The Strategy of Preventing COVID-19 Infection for Dental Clinics in Taiwan - Ya-Ai Cheng; Kuang-Min Hsieh; Sin-Yen Hsieh; Yueh-Tzu Kao (Journal of Dental Problems and Solutions - Peertechz Publications, 2020)
Coronavirus disease 2019 (COVID-19) is spread in the world. To understand how to prevent virus infection in dental clinics, case study is used in this study. Following SARS prevention, measuring body temperature, using mask, using dispersal instruments and spraying 75% alcohol are included. And clinics build standard operation procedure from patient arriving to treatment finished. Recording travel history, arranging the number of patients and accompany person are included. Isolate droplets and avoid the short distance of social contact are applied in the strategy.